2348. Influenza Complications Amongst Pediatric Inpatients in Singapore, a Tropical Country. (26th November 2018) - Chong, Chia Yin; Tan, Natalie Woon Hui; Yung, Chee Fu; Thio, Szu Tien; Gan, Cherie; Tee, Nancy Wen Sin; Lin, Raymond; Thoon, Koh Cheng
Abstract: Background: Influenza is a common cause of morbidity and mortality in children. This was a retrospective study of hospitalized children with influenza at KKH admitted from January 2013 to December 2014 to compare the type of complications by age and underlying medical conditions. Methods: Influenza patients were identified by a positive polymerase chain reaction (PCR) or immunoflourescence antigen from nasopharyngeal swabs. Patients were grouped into neurologic, respiratory, other and no complication. Multinomial regression was used to compare age and complications with underlying disease. Results: There were a total of 1, 272 patients with a median age of 37 months (IQR 13–76 months). Influenza A constituted 76.3% with serotype H3N2 (54.5%), H1N1 (18.2%), unknown (5.4%). Influenza B constituted 22.9% with serotypes: Yamagata (16.3%), Victoria (5.7%). Only 4 patients (0.3%) had sequelae or death. 28% of influenza admissions had complications. The most common being neurologic 44% ( n = 156) followed by respiratory 31% ( n = 110). The most common clinical complications were: febrile seizure 34.1%, bronchitis/bronchiolitis 9.9%, pneumonia 7.3%. There was a significant difference between complications by male gender ( P = 0.001), community acquisition ( P = 0.007), influenza type, other positive viruses, comorbidity, asthma/ lung disease, neurologic disease, history of seizures, ICU/High Dependency admissions (all P ≤ 0.001), developmental delay ( P = 0.002), Kawasaki disease on aspirin ( P = 0.026), gastro-esophageal reflux ( P = 0.034) and prescription of oseltamivir ( P = 0.003). Neurologic complications occurred especially in the 2–< 5 year age group (37.2%), respiratory complications in the 6–23 month age group (39.1%). Age ≥5 year was more likely to have neurologic complication if they had a history of seizures (OR 14.2, P < 0.001). Age ≥2 years was more likely to have respiratory complications if they had asthma/ lung disease (OR 3.5, P < 0.001). Conclusion: Although influenza mortality was low, 28% of influenza admissions in children had significant complications. Children with underlying medical problems should routinely receive influenza vaccinations to avoid complicated influenza illness. Disclosures: All authors: No reported disclosures.